2010
DOI: 10.1111/j.1751-0813.2010.00628.x
|View full text |Cite
|
Sign up to set email alerts
|

Holter monitoring in 36 dogs with myxomatous mitral valve disease

Abstract: Arrhythmias are a common finding in dogs with MMVD and Holter monitoring is a reliable tool for both HR monitoring and diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
41
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 31 publications
4
41
1
2
Order By: Relevance
“…it is known that the variability decreases in the presence of heart failure in dogs with chronic myxomatous mitral valve (Crosara et al, 2010) and in advanced DCM (Calvert and Wall, 2001), and a study of HR variability in cats has not been found yet. Perhaps with more studies, HR variability will be more used in Veterinary Medicine Veterinary medicine is advancing at a very rapid pace, particularly given the breadth of the discipline.…”
Section: Heart Rate Variabilitymentioning
confidence: 99%
“…it is known that the variability decreases in the presence of heart failure in dogs with chronic myxomatous mitral valve (Crosara et al, 2010) and in advanced DCM (Calvert and Wall, 2001), and a study of HR variability in cats has not been found yet. Perhaps with more studies, HR variability will be more used in Veterinary Medicine Veterinary medicine is advancing at a very rapid pace, particularly given the breadth of the discipline.…”
Section: Heart Rate Variabilitymentioning
confidence: 99%
“…One of the studies revealed that a significant percentage (69%) of dogs demonstrated isolated supraventricular premature complexes; however, the Holter monitoring did not indicate trigeminy (CROSARA et al, 2010;RASMUSSEN et al, 2012;OLIVEIRA et al, 2014). Some studies reported the occurrence of trigeminy; however, it was of ventricular origin (CROSARA et al, 2010). In veterinary medicine, there is one report of supraventricular trigeminy in a foal (RISBERG et al, 2005).…”
mentioning
confidence: 99%
“…In studies evaluating cardiac arrhythmias in dogs with MMVD using conventional and Holter (24 hours) ECG, despite the higher incidence of arrhythmias of supraventricular origin, supraventricular trigeminy is not reported. One of the studies revealed that a significant percentage (69%) of dogs demonstrated isolated supraventricular premature complexes; however, the Holter monitoring did not indicate trigeminy (CROSARA et al, 2010;RASMUSSEN et al, 2012;OLIVEIRA et al, 2014). Some studies reported the occurrence of trigeminy; however, it was of ventricular origin (CROSARA et al, 2010).…”
mentioning
confidence: 99%
See 2 more Smart Citations